Interlaminar Shear and Tensile Strengths of the Polymer Composites Based on CNT Films - Aouraghe, Mohamed Amine; Marriam, Ifra; Sun, Lijun; Wang, Yifan; Xu, Fujun; Qiu, Yiping (Journal of Composites and Biodegradable Polymers, 2019)
Carbon nanotubes demonstrate excellent electrical, mechanical and thermal properties due to their unique structure. To bring this astonish properties into macroscale, CNTs were assembled into large scale film via FCCVD method. However, the obtained CNT film mechanical properties remained unsatisfactory and leaves room for further improvement. Herein, different mixtures of Epoxy and PVA polymer matrix were incorporated via vacuum assisted resin transfer molding (VARTM) technique into CNT film and successfully enhanced its mechanical properties. The obtained CNT film/Epoxy and CNT film/PVA tensile strength increased by 3.5 and 4.7 times compared to pristine CNT film tensile strength. In addition, polymer matrix compatibility with CNT film was investigated by interlaminar strength method. CNT films/epoxy composite exhibited significantly higher peeling strength (633.7 N/m) compared to those with PVA (70.8 N/m) demonstrating the good affinity of epoxy with CNT film.